2011
DOI: 10.2136/sssaj2010.0095
|View full text |Cite
|
Sign up to set email alerts
|

Forage Radish Cover Crops Increase Soil Test Phosphorus Surrounding Radish Taproot Holes

Abstract: All rights reserved. No part of this periodical may be reproduced or transmitted in any form or by any means, electronic or mechanical, including photocopying, recording, or any information storage and retrieval system, without permission in writing from the publisher. Permission for printing and for reprinting the material contained herein has been obtained by the publisher.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 34 publications
2
25
1
Order By: Relevance
“…All of these values are below the range of P concentrations in the cover crop shoot biomass sampled in the current study. This is of interest, as a related forage radish, with similar P content, was found to increase P availability in a winter cover cropped system, though this might have been limited to the rooting zone (White and Weil, 2011). Similarly, winter rye was found to increase biomass and P uptake of a subsequent crop of soybean (Karasawa and Takahashi, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…All of these values are below the range of P concentrations in the cover crop shoot biomass sampled in the current study. This is of interest, as a related forage radish, with similar P content, was found to increase P availability in a winter cover cropped system, though this might have been limited to the rooting zone (White and Weil, 2011). Similarly, winter rye was found to increase biomass and P uptake of a subsequent crop of soybean (Karasawa and Takahashi, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…These results are higher than what is found in literature most likely due to higher plant development thanks to the favorable growing conditions. White and Weil (2011) observed that root biomass of daikon radish was around 1 t ha −1 and root P uptake ranged from 3.6 to 7 kg ha −1 . On average, the other species accumulated about 23, 3 and 10 kg ha −1 of N, P and K in their roots.…”
Section: Influence Of Plant Traits On Nutrient Uptakementioning
confidence: 96%
“…Cover crops are known to concentrate P in aboveground biomass prior to cell lysis (Ulen 1997). Radish (Raphanus sativus) cover crops have been shown to concentrate surface soil P within 3 cm (1.2 in) of the senesced radish plants (White and Weil 2011). Winter cover has been shown to increase SP loads more than 200% and TP 160% compared to no winter cover (Liu et al 2014).…”
Section: Runoffmentioning
confidence: 99%